Studies in Deuteronomy - von Rad, Gerhard, 1901-1971; Stalker, David M.G. (London, UK SCM, 1953)
Includes bibliographical references and index.
Originally published in German: Deuteronomium-Studien.--Gottingen : Vanenhoeck and Ruprecht, 1948.
Keywords: Bible. O.T. Deuteronomy -- commentaries